Effect of bacterial growth period on the sensitivity of the MTT assay for silver - Halmi, MIE; Ahmad, F; Hashim, AK; Shamaan, NA; Syed, MA; Shukor, MY (Triveni Enterprises, 2024)
Respiratory activity inhibition by toxic compounds in bacteria and yeast has been used to detect toxic compounds in the environment. Often the age of culture contributes towards the sensitivity of detection. In the present work, the effect of growth period on the sensitivity of an inhibitive assay for heavy metals using bacterial respiratory assay system based on the reduction of the water soluble tetrazolium dye MU is reported. A silver-sensitive isolate was discovered to exhibit different sensitivities towards silver at different growth periods. An exponential decay model adequately described the inhibition due to silver. Analysis using ANOVA with post-hoc Tukey's test showed that the IC50 obtained by strain DRYS8 grown at the 12 hr-period in nutrient broth at 28 degrees C gave the lowest value compared to other growth periods. This study highlights the importance of taking into accounts growth conditions and age of culture in developing cellular-based bioassays.